2016
DOI: 10.21107/jk.v9i1.1019
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversitas Dan Populasi Ikan Karang Di Perairan Selat Sempu Sendang Biru Kabupaten Malang Jawa Timur

Abstract: Reef fish is one of the conspicuous inhabitant in the reef

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
6
0
2
Order By: Relevance
“…Here, we also overlayed the results with previous studies that carried out underwater surveys in the waters around the port and Sempu Island (Luthfi et al 2016). This reported that only gathered three families marine fish which included in this eDNA metabarcoding list result.…”
Section: The Edna Metabarcoding Analysismentioning
confidence: 66%
See 1 more Smart Citation
“…Here, we also overlayed the results with previous studies that carried out underwater surveys in the waters around the port and Sempu Island (Luthfi et al 2016). This reported that only gathered three families marine fish which included in this eDNA metabarcoding list result.…”
Section: The Edna Metabarcoding Analysismentioning
confidence: 66%
“…Tables and figures of data were performed by Excel 2010, similarity and biodiversity analysis using Primer v7 program. The data on the common local name of fish landed in Pondok Dadap fish station was provided by the East Java Province's Office of Marine and Fisheries, and also previous study using Underwater Visual Census (UVC) around Sendang Biru, Malang by (Luthfi et al 2016). Phylogenetic tree constructed by Mega7 (Kumar et al 2016) using Neighbor-Joining algorithm both eDNA sequences results.…”
Section: Discussionmentioning
confidence: 99%
“…Ikan mayor secara umum lebih banyak jumlahnya dari jenis ikan karang yang lain, dari hasil pengamatan diperoleh jenis ikan mayor dari famili Pomacentridae (ikan betok laut), Labridae (ikan sapu-sapu), dan Blenniidae (ikan peniru). Menurut Luthfi et al (2016) jenis ikan dari famili scaridae bersifat herbivora, memiliki peran yang penting di ekosistem terumbu karang, karena keberadaan ikan ini akan mengontrol pertumbuhan alga di terumbu karang.…”
Section: Kondisi Ikan Karangunclassified
“…Unfortunately, despite being established as Nature Reserve Area (id: Cagar Alam) since colonial period through Besluit van den Gouverneur Generaal van Nederlandsch Indie No: 69 and No.46 dated March 15 th 1928 about Aanwijzing van het natourmonument Poelau Sempoe, the overall biodiversity of this Nature Reserve and the area around its proximity, both above and below the waters is still much unknown. There are some studies conducted around this area to assess the general status of reef fishes [13][14] and invertebrates [7] [15] but the information provided is still insufficent for underwater macro photography activity because it is only cover the most common fishes and invertebrates species. Therefore, to improve the knowledge about uncommon recorded, and possibly rare species that attract underwater macrophotographers alike, we conducted this comprehensive study to assess the diversity of cryptic marine fauna on the proximity of coral reef area at Sempu Strait to provide better information and to bring up its underwater macrophotography tourism potential.…”
Section: Introductionmentioning
confidence: 99%